2015
DOI: 10.1002/pts.2132
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Crude Extracts of Coffee and Spent Coffee Ground on Areca Palm Leaf Sheath (Areca catechu) Based Food Packaging

Abstract: This study observed the antifungal activity of crude coffee extract (CCE) and crude spent coffee ground extract (CSCGE) against Aspergillus sp., Aspergillus flavus, Aspergillus niger, Penicillum citrinum, Penicillum chrysogenum and Eurotium amstelodami on the surface of an areca palm leaf sheath (Areca catechu). The agar dilution method was employed to determine the minimal inhibitory concentration (MIC) of the CCE for the first, second and third extractions and CSCGE for the first and second extractions in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…The two peaks between 2950 cm −1 and 2850 cm −1 are associated with the asymmetric and symmetric C−H methyl and methylene stretching groups present in the spectra for cellulose in Figure A2. The bands at 1665-1645 cm −1 in the cellulose spectrum have been reported to be a hydrogen bonding coupled with COO¯ of the cellulose [40]. The vibrations at around 1600 cm −1 and 1555 cm −1 have a high pyramidic character in caffeine and decreases the stretching vibrations (ʋ) of the C=C and C=N bond.…”
Section: Analysis Of Cellulose After Reaction With Caffeinementioning
confidence: 99%
See 1 more Smart Citation
“…The two peaks between 2950 cm −1 and 2850 cm −1 are associated with the asymmetric and symmetric C−H methyl and methylene stretching groups present in the spectra for cellulose in Figure A2. The bands at 1665-1645 cm −1 in the cellulose spectrum have been reported to be a hydrogen bonding coupled with COO¯ of the cellulose [40]. The vibrations at around 1600 cm −1 and 1555 cm −1 have a high pyramidic character in caffeine and decreases the stretching vibrations (ʋ) of the C=C and C=N bond.…”
Section: Analysis Of Cellulose After Reaction With Caffeinementioning
confidence: 99%
“…The holistic infrared spectrum of the mixture with caffeine and cellulose fibers (see Appendix A, Figure A2) showed peaks typical of a cellulosic substrate. At around 3400 cm −1 , it can be observed that there was a strong broad band corresponding to different O-H stretching modes [40].…”
Section: Analysis Of Cellulose After Reaction With Caffeinementioning
confidence: 99%
“…Lo anterior determinó que el hongo más resistente fue A. flavus y que los extractos CCE fueron más efectivos contra los hongos evaluados que los CSCGE, lo cual depende en gran parte de la polaridad de los solventes usados para la extracción, ya que hay compuestos, como los alcaloides, que no pueden disolverse bien en agua. En este estudio fue posible evaluar en condiciones in vivo la actividad antifúngica de los extractos, se realizaron pruebas en la superficie de vainas de hojas de palma areca durante el almacenamiento, en donde se observó una inhibición total del crecimiento de los hongos mediante la segunda extracción de CSCGE a 460 µg/ ml durante 21 días, lo cual fue disminuyendo hasta el día 42, cuando no pudo evitarse el crecimiento de los hongos; mientras que en el tratamiento control los hongos crecieron en un lapso de 3 días, demostrando que estos extractos pueden alargar la vida útil no solo de las hojas de palma, sino de otras plantas y alimentos (Nonthakaew et al, 2015). Lo anterior demuestra que el uso de extractos de pulpa de café puede utilizarse para controlar el crecimiento y desarrollo de agentes microbianos.…”
Section: Actividad Antimicrobiana De La Pulpa De Café Y Sus Componentesunclassified
“…[ 175 ]. Shelf life of durian paste product wrapped with areca palm leaf sheath treated with spent coffee ground extracts was extended from three days to 21 days under the storage condition of 30 °C [ 176 ].…”
Section: Main Applications Of Phenol-based Polymers In Food and Hementioning
confidence: 99%